Monitoring foods and beverages provided and sold in public sector settings. (17th September 2013) - L'Abbé, M.; Schermel, A.; Minaker, L.; Kelly, B.; Lee, A.; Vandevijvere, S.; Twohig, P.; Barquera, S.; Friel, S.; Hawkes, C.; Kumanyika, S.; Lobstein, T.; et al.
Summary: This paper outlines a step‐wise framework for monitoring foods and beverages provided or sold in publicly funded institutions. The focus is on foods in schools, but the framework can also be applied to foods provided or sold in other publicly funded institutions. Data collection and evaluation within this monitoring framework will consist of two components. In component I, information on existing food or nutrition policies and/or programmes within settings would be compiled. Currently, nutrition standards and voluntary guidelines associated with such policies/programmes vary widely globally. This paper, which provides a comprehensive review of such standards and guidelines, will facilitate institutional learnings for those jurisdictions that have not yet established them or are undergoing review of existing ones. In component II, the quality of foods provided or sold in public sector settings is evaluated relative to existing national or sub‐national nutrition standards or voluntary guidelines. Where there are no (or only poor) standards or guidelines available, the nutritional quality of foods can be evaluated relative to standards of a similar jurisdiction or other appropriate standards. Measurement indicators are proposed (within 'minimal', 'expanded' and 'optimal' approaches) that can be used to monitor progress over time in meeting policy objectives, and facilitate comparisons between countries.